ENERGY DISPERSIVE X-RAY MICROANALYSIS (EDX) OF SCALE OF SCHISTURA MONTANUS (MCCLELLAND, 1838) - R. K. NEGI; SHEETAL MAMGAIN (The Bioscan, 2011)
The scale of Schistura montanus (McClelland) was found to be oval in shape. The scale contains nine minerals, viz. Ca, P, Na, Si, Mg, S, Cl, Al and O. The percentage composition of Ca was reported maximum followed by phosphorus, Na, Si and Mg.